Do non-performing loans matter for bank lending and the business cycle in Euro area countries? - Ivan Huljak; Reiner Martin; Diego Moccero; Cosimo Pancaro (Journal of Applied Economics, 2022)
We estimate the impact of changes in non-performing loan (NPL) ratios on aggregate banking sector variables and the macroeconomy by estimating a panel Bayesian VAR model for twelve euro area countries. The main findings are as follows: i) An impulse response analysis shows that an exogenous increase in the change in NPL ratios tends to depress bank lending volumes, widens bank lending spreads and leads to a fall in real GDP growth and residential real estate prices; ii) A forecast error variance decomposition shows that shocks to the change in NPL ratios explain a relatively large share of the variance of the variables in the VAR, particularly for countries that experienced a large increase in NPL ratios during the recent crises; and iii) A three-year structural out-of-sample scenario analysis suggests that reducing banks' NPL ratios can produce significant benefits in terms of improved macroeconomic and financial conditions.
Keywords: 330; Euro area countries; hierarchical priors; non-performing loans; panel Bayesian VAR